Smart phone casing (SCase) / Ahmad Tarmizi Sazali … [et al.] - Sazali, Ahmad Tarmizi; Abu Zahar, Muhammad Zaim; Samiran, Noor Shahira; Jeffery, Nur Shafira (2019)
Smart Case (SCase) is a smart phone casing that have more safety features compare to the current phone casing. The Smart Case (SCase) phone casing will protect mobile phones in more appropriate way because it has a thumbprint technology, 'pop up' features if the mobile phone falls down, torchlight and power bank with 3000 MaH.